2020
DOI: 10.3390/pathogens9060438
|View full text |Cite
|
Sign up to set email alerts
|

Human T leukaemia Type 1 and COVID-19

Abstract: In the absence of clinical data on Human T leukaemia Type 1 and COVID-19 infection, we are providing guidance to clinicians who look after people living with HTLV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…COVID-19 in individuals with human T-cell lymphotropic virus 1 type-1 (HTLV-1) infection, and a need for guidance on management of patients with HTLV-1 and COVID-19 coinfection. 2 Herein, we report a fatal case of COVID-19 in a previously undiagnosed HTLV-1 carrier.…”
mentioning
confidence: 93%
“…COVID-19 in individuals with human T-cell lymphotropic virus 1 type-1 (HTLV-1) infection, and a need for guidance on management of patients with HTLV-1 and COVID-19 coinfection. 2 Herein, we report a fatal case of COVID-19 in a previously undiagnosed HTLV-1 carrier.…”
mentioning
confidence: 93%
“…With the advent of the COVID-19 pandemic and governmental guidelines recommending social distancing, EBMSP implemented a contingency plan for employees, students, and patients [ 15 ], which made it impossible for patients to be seen at CHTLV. Despite the fact that no reports have indicated that COVID-19 may be more severe in patients infected with HTLV-1, special care recommendations have been published for this group, since this infection predominantly affects older individuals for whom comorbidities such as diabetes, systemic arterial hypertension, and overweight are frequent [ 16 ]. Moreover, it has been reported that HTLV-1-infected individuals may present some degree of immunosuppression, since several infectious diseases, such as tuberculosis, strongyloidiasis, and scabies, are more frequent or more severe in these individuals [ 9 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…This information is still scarce and is under study. 11 This article will explain the experience during these two years of the pandemic with HTLV-1 patients in our cohort and concomitant SARS-CoV-2 infection in this type of patient.…”
Section: Introductionmentioning
confidence: 99%